Bone-specific master transcription factor Runx2 regulates signaling and metabolism related programs in osteoprogenitors - Teplyuk, N.M.; Teplyuk, V.I. (Вiopolymers and Cell, 2010)
Aim. Runx2 (AML3) transcription factor is the key regulator of osteoblastic lineage progression and is indispensable for the formation of mineral bones. Runx2 expression increases during differentiation of osteoblasts to induce osteoblast-specific genes necessary for the production and deposition of bone mineral matrix. However, Runx2 is also expressed at a lower level in early osteoprogenitors, where its function is less understood. Here we study how Runx2 determines the early stages of osteoblastic commitment using the model system of Runx2 re-introduction in mouse calvaria cells with Runx2 null background. Method. Affymetrix analysis, Western blot analysis and quantitative real-time reverse transcriptase PCR (qRT-PCR) analysis were employed. Results. Gene expression profiling by Affymetrix microarrays revealed that along with the induction of extracellular matrix and bone mineral deposition related phenotypic markers, Runx2 regulates several cell programs related to signaling and metabolism in the early osteoprogenitors. Particularly, Runx2 regulates transcription of genes involved in G-protein coupled signaling network, FGF and BMP/TGF beta signaling pathways and in biogenesis and metabolism pathways of steroid hormones. Conclusion. The data indicate that the lineage specific program, regulated by the master regulatory transcription factor, includes the regulation of cellular signaling and metabolism which may allow the committed cell to react and behave differently in the same microenvironment. Транскрипційний фактор Runx2 (AML3) є важливим регулятором диференціації остеобластів, необхідним для формування кісток. Експресія гена Runx2 зростає в процесі диференціації остеобластів і призводить до активації остеобласт-специфічних генів, відповідальних за продукування мінерального матриксу. Мета роботи полягала у визначенні функції гена Runx2 у попередниках остеобластів, де він експресується на досить низькому рівні. Методи. Ми дослідили функцію гена Runx2 на ранніх стадіях розвитку остеобластів за допомогою модельної системи Runx2-нокаутних клітин скальпів мишей, яким вводили ген Runx2. Результати. При дослідженні експресії геному за допомогою чипів Affymetrix виявлено, що разом із індукцією фенотипових маркерів відкладання зовнішньоклітинного мінерального матриксу ген Runx2 регулює декілька генетичних програм, пов’язаних із сигналінгом і метаболізмом попередників остеобластів. Зокрема, Runx2 регулює гени сигнальної мережі, зчепленої з G-білками, сигнальні шляхи FGF, BMP/TGF, а також ферментативні системи біосинтезу і метаболізму стероїдних гормонів. Висновки. Отримані дані вказують на те, що частина програми спеціалізації, яку виконує ключовий транскрипційний фактор, складається з програмування сигнальних шляхів та метаболізму клітини, дозволяючи ранньоспеціалізованій клітині реагувати та функціонувати певним чином у мікросередовищі. Транскрипционный фактор Runx2 (AML3) является ключевым регулятором дифференциации остеобластов, необходимым для формирования костей. Экспресия гена Runx2 повышается в процессе дифференциации остеобластов, где он активирует остеобласт-специфические гены, необходимые для продукции минерального матрикса. Цель работы состояла в определении функции гена Runx2 в ранних предшественниках остеобластов, где он экспрессируется на достаточно низком уровне. Методы. Мы исследовали, как Runx2 функционирует на ранних стадиях специализации остеобластов с помощью модельной системы внедрения Runx2 в Runx2-нокаутные клетки скальпа мыши. Результаты. При изучении экспресии генома с помощью чипов Affymetrix обнаружено, что вместе с индукцией фенотипичных маркеров, отвечающих за продукцию внеклеточного матрикса, Runx2 регулирует несколько генетических программ, связанных с сигналингом и метаболизмом остеобластов. В частности, Runx2 регулирует гены сигнальной сети, сцепленной с G-белками, сигнальных путей FGF, BMP/TGF, а также системы биосинтеза и метаболизма стероидных гормонов. Выводы. Полученные данные указывают на то, что программа специализации, выполняемая ключевым транскрипционным фактором, включает программирование сигнальных путей и метаболизма клетки, позволяя раннедифференцированной клетке вести себя определенным образом в идентичной микросреде.